Synthesis and evaluation of a potent, well-balanced EP2/EP3 dual agonist. Issue 1 (1st January 2018) - Kinoshita, Akihiro; Higashino, Masato; Yoshida, Koji; Aratani, Yoshiyuki; Kakuuchi, Akito; Hanada, Keisuke; Takeda, Hiroyuki; Naganawa, Atsushi; Matsuya, Hidekazu; Ohmoto, Kazuyuki
Graphical abstract: Abstract: A highly potent and well-balanced dual agonist for the EP2 and EP3 receptors is described. Optimization of the lead compound was accomplished in consideration of the relative agonist activity against each EP subtype receptor and the pharmacokinetic profile. As the result, 2-[(2-{(1 R, 2 R )-2-[(1 E, 4 S )-5-cyclopentyl-4-hydroxy-4-methyl-1-penten-1-yl]-5-oxocyclopentyl}eth-yl)thio]-1, 3-thiazole-4-carboxylic acid (10 ) showed excellent potency (human EC50 EP2  = 1.1 nM, EP3  = 1.0 nM) with acceptable selectivity over the EP1 and EP4 subtypes (>2000-fold). Further fine-tuning of compound10 led to identification ofONO-8055 as a clinical candidate.ONO-8055 was effective at an extremely low dose (0.01 mg/kg, po, bid) in rats, and dose-dependently improved voiding dysfunction in a monkey model of underactive bladder (UAB).ONO-8055 is expected to be a novel and highly promising drug for UAB.